Analisis Pemasaran dan Nilai Tambah Abon Ikan Cakalang: Studi Kasus di UMKM Wadimah - Junianto Junianto; Fadhlu Razaaq Nihe; Viola Adriany Savitri; Friyona Dewi Fortuna (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
The development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia has received special attention from various parties. One of the MSMEs that is developing rapidly in West Java is the Wadimah MSME, which is engaged in processing skipjack tuna floss. This research aims to analyze the marketing management carried out by Abon Wadimah MSMEs and the added value obtained from processing skipjack tuna into shredded fish. Marketing management analysis includes market segmentation, product pricing, promotion-distribution, and competitors. The method used is a descriptive method and added value analysis using the hayami method. Based on research results, it shows that Wadimah MSMEs in marketing skipjack tuna floss, the market segmentation is children to adults. Product pricing is determined using a combined method of cost plus pricing and loss leader pricing. Promotion is carried out through social media, namely WhatsApp, Instagram and Google Business. The competition that occurs in the marketing of Wadimah UMKM shredded skipjack is perfect competition. The added value from the processing of skipjack tuna into shredded fish carried out by Wadimah MSMEs is at a high value added ratio, namely 58.1%.